Idiopathic choroidal neovascular membrane in a young female - Saad Abdullah Waheeb; Mahmood Jameel Showail (Oman Journal of Ophthalmology, 2009)
A case of idiopathic choroidal neovascular membrane (CNVM) is described in a 17-year-old female patient. On initial examination her vision was counting fingers at one meter in the left eye (OS) and Fluorescein angiography showed a well-defined hyperfluorescent area corresponding to the CNVM. Intravitreal bevacizumab was injected into OS, and at a five-week follow-up visit, visual acuity improved to 20/100 OS. This case is unusual, in that the CNVM developed in a young lady with no significant past medical history and with the absence of a choroidal or retinal pigment epithelial disease process that may be associated with a CNVM.